Research on NVIDIA's Development Strategy - Zhang, Rui; Hu, Lei (International Journal of Global Economics and Management, 2024)
NVIDIA, as the world's leading supplier of graphics processing units (GPUs) and artificial intelligence (AI) computing hardware, has achieved rapid development and expansion in recent years. This paper studies the evolution of NVIDIA's development strategy and the factors for its success by analyzing NVIDIA's development history, industry environment and competitive landscape. At the same time, this paper also explores the challenges faced by NVIDIA and the direction of its future development.